The trans guide to mental health and well-being - Lees, Katy (Jessica Kingsley Publishers, 2022)
This empowering self-help guide provides advice and strategies for trans and/or non-binary people on a range of common mental health issues including anxiety, depression, body image, trauma, suicidal thoughts and dissociation. It provides advice on neutralising negative thoughts, coping with transphobia, coming out, dealing with imposter syndrome, and implementing achievable self-care strategies and mindfulness techniques." --